Cigarette Smoking and Skin Prick Test in Patients With Allergic Rhinitis - Khazaei, Hossein Ali (Int J High Risk Behav Addict, 2015)
BACKGROUND: Allergic Rhinitis (AR) is the most common allergic disease, affecting 30% of population around the world. The disease is predominantly associated with exposure to some aeroallergens like cigarette smoking. Skin Prick Test (SPT) is a method of detecting immediate allergic reactions and is applied for controlling disease and therapeutic modality. OBJECTIVES: This study was designed to investigate the effect of cigarette smoking on SPT results among male and female individuals with AR disease. PATIENTS AND METHODS: A total of 478 patients with AR admitted to the 2 main hospitals of Zahedan City from 2005 to 2012, were recruited in this analytic-descriptive study. Categories of smokers and never smokers were used based on patient’s statements and their history of smoking. SPT was performed with panel of some allergens and results were recorded and analyzed statistically. Odds ratio and confidence interval method were calculated using univariate logistic regression. RESULTS: The results of this study indicated that 41.4% of patients with allergic rhinitis was smoker with ages ranged from 15 to 70 years. The result of this study also showed that smoking has no effect on SPT results of pollen and weeds aeroallergens conducted on male and female AR patients. However, male were significantly more sensitive than female in terms of sensitivity to the aspergillus, cladosporium, house dust mite, grasses, wheat, cockroach, and feather allergens. CONCLUSIONS: Our findings did not support the effect of cigarette smoking on SPT reactivity to pollen and weeds aeroallergens. However, male were significantly more sensitive than female in terms of sensitivity to some allergens.